Prolonged use of Kinesiotaping does not enhance functional performance and joint proprioception in healthy young males : randomized controlled trial - Magalhães, Igor (2016)
Objectives: the aim of this study was to investigate the effects of continuous (48-hour) use of Kinesiotaping (KT) on functional and proprioceptive performance in healthy, physically active men. Method Twenty-six healthy, physically active men (21.8±2.2 years old) were randomly allocated into two groups: 1) Kinesiotaping group (KG, tape applied with 40% tension for rectus femoris activation); 2) Control (CG, tape applied over rectus femoris without additional tension). Subjects attended the laboratory on five separate occasions: 1) familiarization; 2) baseline measurement without tape (BL); 3) immediately post-tape application (T0); 4) 24h (T24); and 5) 48h (T48) post-tape application. The outcomes were distance in the single (SHT) and triple hop tests (THT), vertical jump height (VJH), vertical jump power (VJP), and rate of force development (RFD). A mixed-model ANOVA was applied to verify differences between and within groups. Results No significant (p >0.05) differences were found in the SHT and THT between groups and moments. Likewise, the main effects for VJH, VJP, and RFD were not significant (p >0.05). Conclusion The present study demonstrated no significant immediate or prolonged (48h) effects of KT on functional and proprioceptive performance.